Pemanfaatan Website Profile Sebagai Peningkatan Sarana Promosi Digital - Chaska Andra Praditya; Sri Siswanti; Andriani Kusumaningrum; Setiyowati Setiyowati; Hasman Budiadi (JPM: Jurnal Pengabdian Masyarakat, 2026)
Make Up Artist (MUA) Aprilianafast, a makeup service business located in Klaten and its surroundings. In the MUA service sector, especially in areas such as Klaten and its surroundings, competition is very tight. Customers currently tend to search for information, view portfolios, and compare services online before choosing a MUA. The background of this activity is based on the absence of centralized official digital media, so information about profiles, portfolios, services, and prices is still scattered on social media and difficult to access in a structured manner by potential clients. The purpose of this activity is to assist in creating a profile website that will be used to disseminate information about services at MUA Aprilianafast. The implementation method includes: Needs analysis to identify key content relevant to the target audience; website design to compose a navigation structure; visual design according to brand identity; implementation and testing, namely, to develop the website and then conduct black box testing to ensure the function runs well. Interface design prioritizes the principles of user experience (UX) and user interface (UI) with a responsive design and in accordance with the visual identity of the beauty industry. The resulting MUA profile website provides information about the MUA's profile, portfolio, services and pricing, testimonials, and contact information. Black-box testing of the profile website showed that all key functions worked as designed.